2022
DOI: 10.1002/pits.22819
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory focus and creativity: Adaptive‐innovative cognitive style as a mediator and school climate as a moderator

Abstract: This study examined the relationship between regulatory focus and creativity in combination with adaptive‐innovative cognitive style and school climate. A total of 687 middle school and high school students (Mage = 13.98 years; 52.8% males) completed a creative task and questionnaires concerning regulatory focus, adaptive‐innovative cognitive style, school climate, and creativity. Structural equation modeling (SEM) revealed that promotion focus positively predicted creativity through innovative style and negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 120 publications
0
2
0
Order By: Relevance
“…Previous research suggests that in the process where school climate acts as a moderator, two different patterns may emerge: the "boosting effect" and the "diminishing effect" patterns [50][51][52]. These patterns illustrate how protective factors operate in different risk environments using the moderating role of school climate in the relationship between cumulative family risk and core self-evaluation/depression as an example.…”
Section: The Moderating Role Of School Climatementioning
confidence: 99%
“…Previous research suggests that in the process where school climate acts as a moderator, two different patterns may emerge: the "boosting effect" and the "diminishing effect" patterns [50][51][52]. These patterns illustrate how protective factors operate in different risk environments using the moderating role of school climate in the relationship between cumulative family risk and core self-evaluation/depression as an example.…”
Section: The Moderating Role Of School Climatementioning
confidence: 99%
“…Besides, Hui (2021) revealed that higher perspective-taking and promotion enhance creativity. Also, Wang et al (2022) pointed out that promotion focus positively predicted creativity through innovative style and negatively predicted creativity through adaptive style, and prevention focus negatively predicted creativity through adaptive style. Wang et al (2021) found an indirect relationship between regulatory focus and creativity through the mediation of intrinsic motivation.…”
Section: Theoretical Background Problem-solving In Educational Settingsmentioning
confidence: 99%